Modellierung der Stoffübertragung beim Niederdruckcarbonitrieren mit Ammoniak und Acetylen - Hagymási, László (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
A mathematical model has been developed for the description of the transport process for low-pressure carbonitriding with ammonia and acetylene. As an example the case hardening steel 18CrNi8 was used. It can be shown that the concentration profiles of carbon and nitrogen as well as the ammonia exhaust gas concentration are described well. Based on the modelling, first simulation runs could be carried out for further optimization of the heat treatment process.